Method for the discovery of IPv6 DNS services based on the dynamic domain name watermarks - HAN Dingkang; ZHU Yujia; ZHAO Lei; JIAO Liang; LIU Qingyun (网络与信息安全学报)
DNS (domain name system) services in the IPv6 environment experienced rapid development. Research on methods for discovering DNS services in an IPv6 environment was of paramount importance in order to analyze the global developmental trends of DNS services in IPv6 and enhance their reliability. Based on the cooperative resolution relationship between IPv4 and IPv6, associating IPv6 DNS services through inter-stack services was an effective approach. However, existing methods for discovering IPv6 DNS services based on inter-stack service association were limited by the length of DNS probe packets. In response to this issue, a novel approach was proposed for discovering IPv6 DNS services based on dynamic domain name watermarks. By constructing dynamic domain name resource records using self-established authoritative servers, the limitations imposed by probe packet length were circumvented. Comparative analysis indicated that the number of discovered IPv6 DNS services using this method increased by nearly 98% compared to traditional methods. Moreover, through the analysis of watermark logs, a plethora of resolver dependencies and centralization phenomena were identified.